2009
DOI: 10.1136/ard.2009.117234
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of recombinant human cartilage glycoprotein-39 as a treatment for rheumatoid arthritis: a phase II, multicentre, double-blind, randomised, placebo-controlled, parallel-group, dose-finding trial

Abstract: It was concluded that with the treatment protocol used (dose levels and frequency of dosing), intranasal treatment with Org 39141 was safe but did not result in more clinical improvement than in placebo-treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Several drugs in development have targeted recently identified pathways7 8; however, not all have shown efficacy 9. Trial designs such as ours will help shorten the development process.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs in development have targeted recently identified pathways7 8; however, not all have shown efficacy 9. Trial designs such as ours will help shorten the development process.…”
Section: Discussionmentioning
confidence: 99%
“…Oral delivery of this peptide led to improved clinical responses and a shift from inflammatory to regulatory cytokine production. By contrast, intranasal delivery of a potential RA autoantigen, human cartilage glycoprotein-39, failed to provide any additional benefit compared to placebo [26]. More recent phase 1 studies in RA patients, and also in diabetic patients, have delivered the tolerising antigen using patient derived APCs.…”
Section: Autoimmune Diseasementioning
confidence: 79%
“…We demonstrated that antigen‐specific T cells themselves express HC gp‐39 in the early phase of arthritis. Intranasal administration of HC gp‐39 was also conducted in human RA, but in Phase II the treatment lacked efficacy when compared with the placebo . We need to further characterize whether human antigen‐specific T cells express HC gp‐39 in the induction phase of RA.…”
Section: Discussionmentioning
confidence: 99%